Effects of extracellular metabolic acidosis on the homeostasis of intracellular pH in hippocampal neurons - Bouyer, Patrice G.; Occhipinti, Rossana; Taki, Sara; Moss, Fraser J.; Boron, Walter F. (Frontiers in Physiology, 2025)
This Hypothesis & Theory contribution accompanies the research paper by Bouyer et al. (Frontiers in Physiology 2024), the first to employ out-of-equilibrium (OOE) CO2/HCO3− solutions to examine systematically the intracellular pH (pHi) effects of extracellular (o) metabolic acidosis (MAc) and its components: an isolated decrease in pHo (pure acidosis, pAc) and an isolated decrease in [HCO3−]o (pure metabolic/down, pMet↓). In this study, after reviewing various types of acid–base disturbances and the use of OOE solutions, we discuss pHi “state” (ΔpHi, in response to a single acid–base challenge) and “behavior” (the ΔpHi transition observed between two successive challenges), along with approaches for quantifying state and behavior. We then discuss the molecular basis of how individual extracellular acid–base disturbances influence pHi via effects on—and interactions among—acid–base transporters, acid–base sensors, and cellular constitution. Next, we examine the determinants of states and behaviors, their impact on the buffering of extracellular acid loads, and how variability in state and behavior might arise. We conclude with a consideration of how mathematical models—despite their inherent limitations—might assist in the interpretation of experiments and qualitative models presented in this study. Among the themes that emerge are (1) hippocampal neurons must have distinct sensors for pHo and [HCO3−]o; (2) these pHo- and [HCO3−]o-driven signal transduction pathways produce additive pHi effects in naïve neurons (those not previously challenged by an acid–base disturbance); and (3) these pathways produce highly non-additive pHi effects in neurons previously challenged by MAc.